Strengthening Financial Literacy for Palm Sugar Farmers in Lombok Island - Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Faturrahman; Baiq Santi Rengganis (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The growth and development of technology in everyday life has the potential to improve people's welfare. The level of public understanding of financial literacy is very important because it plays a role in financial management. The people in Kekait Village have utilized the Aren plant as a source of family income. The knowledge level of digital financial literacy in palm sugar farmers still needs strengthening. Therefore, community service activities were carried out in the form of strengthening digital financial literacy for palm sugar farmers in Kekait Village, Gunungsari District, West Lombok Regency. Based on the community service activities that have been carried out, it can be seen that partners have given positive responses, including: acquiring new knowledge regarding digital financial literacy and digital financial platforms; the community wants to immediately implement good financial planning and management and intend to have digital savings. Sustainability of this activity is needed as a form of monitoring and evaluation of assistance in an effort to provide solutions to problems faced by partners.